2015
DOI: 10.3233/jrs-150709
|View full text |Cite
|
Sign up to set email alerts
|

Decision support systems in clinical practice: The case of venous thromboembolism prevention

Abstract: Coverage of hospitalized patients with documented VTE risk assessment gradually increased after the CDSS implementation, but remained at a low level (19% of eligible patients). Partly it may be attributed to the lack of CDSS integration in electronic health record or computerized physician order entry systems that would facilitate routine documentation of VTE and bleeding risks. However, the introduction of CDSS has allowed reducing significantly the rate of hospital-acquired VTE. This can be explained by draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
1
4
0
5
Order By: Relevance
“…A study performed at a community hospital in New York reported a significant improvement in HCV screening rates from 47% to 88% with electronic interventions; however, this was done using an opt‐out approach for inpatient admissions, a significantly different methodology and population. What is clear, though, is that an overuse of such a system can result in “alert fatigue” and hence have a limited impact. It is important to note that these types of alerts are distinct from electronic triggers of abnormal test results, which have been successful in reducing delays in follow‐up care.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed at a community hospital in New York reported a significant improvement in HCV screening rates from 47% to 88% with electronic interventions; however, this was done using an opt‐out approach for inpatient admissions, a significantly different methodology and population. What is clear, though, is that an overuse of such a system can result in “alert fatigue” and hence have a limited impact. It is important to note that these types of alerts are distinct from electronic triggers of abnormal test results, which have been successful in reducing delays in follow‐up care.…”
Section: Discussionmentioning
confidence: 99%
“…O TEV é um evento muitas vezes silencioso, que não só impõe substancial carga socioeconômica aos sistemas de saúde, mas também é responsável por gerar situações debilitantes para a saúde, tais como aumento da morbimortalidade, incapacidade e diminuição da qualidade de vida (13) . De acordo com evidências científicas, um em cada seis casos de tromboembolismo poderiam ser evitados (14) .…”
Section: Discussionunclassified
“…A avaliação do risco de TEV representa um importante indicador de qualidade dos serviços de saúde (15)(16) . A padronização de modelos de estratificação de risco é um dos principais pontos que estimulam o cenário de pesquisa, visando a adequação da profilaxia centrada no indivíduo e a otimização entre o processo de estratificação e a implementação de medidas preventivas (14) .…”
Section: Discussionunclassified
“…Для аудита назначений АК была использована система автоматизации клинических руководств и аудита лечения (САКРАЛ), разработанная ранее в ММЦ. Принципы ее работы описаны в предыдущих публикациях [14,16]. Модуль «Антикоагулянтная терапия у пациентов с венозными тромбоэмболиями и фибрилляцией предсердий» был разработан на основе клинических рекомендаций Российского кардиологического общества [17] Для аудита антикоагулянтной терапии (АКТ) у пациентов с ФП и ТГВ клинические рекомендации были разделены на 3 раздела: 1) показания/противопоказания к назначению АК; 2) выбор АК и 3) режим дозирования АК (доза и длительность приема АК).…”
Section: система поддержки принятия решенийunclassified
“…Увеличение до 90,6% охвата профилактикой внутригоспитальных венозных тромбоэмболических осложнений (ВГ-ВТЭО) описано при внедрении СППР "Advanced electronic alerts" (eAlerts) [13], которая автоматически формирует напоминание о необходимости тромбопрофилактики после внесения данных в электронную историю болезни. Описана отечественная СППР по профилактике ВГ-ВТЭО, внедрение которой в совокупности с организационными мероприятиями привело к увеличению охвата пациентов тромбопрофилактикой с 15% до 80% (p<0,0001) и статистически значимому сокращению частоты ВГ-ВТЭО [14].…”
unclassified